Dynamic ℒ2 output feedback control of delayed linear parameter varying systems with piecewise constant parameters: A clock‐dependent L–K approach. (2nd December 2020) - Zakwan, Muhammad; Ahmed, Saeed; Bajcinca, Naim
Abstract: This article proposes a new clock‐dependent gain‐scheduled dynamic output feedback controller for delayed linear parameter varying systems with piecewise constant parameters. The proposed controller guarantees ℒ 2 ‐performance. By employing a clock‐dependent Lyapunov–Krasovskii functional, a sufficient condition for the existence of the controller is provided in terms of clock‐ and parameter‐dependent linear matrix inequalities. A case study on output feedback control of delayed switched systems is also provided. To illustrate the efficacy of the result, it is applied to a practical VTOL helicopter model.